2012
DOI: 10.7906/indecs.10.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Personality Traits of the Urban Poor Concerning Solid Waste Management and Household Income and Education

Abstract: This study analyzes the relationship between knowledge, attitude, and behaviour of the urban poor householders concerning solid waste management systems and monthly household income and education. To attain the objective, the study employed statistical techniques such as t-tests of equality of means, one-way ANOVA,  2 "likelihood ratio" test and simple descriptive statistics. The findings show that the urban poor communities with low income and education have been proven to behave in ways matching with and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research on solid waste management behavior consistently highlighted income, education, location, and employment status as key factors. Studies using logistic regression analysis indicated that income predominantly influenced waste generation and households' willingness to minimize waste [43][44][45]; while education positively correlated with recycling behavior [44][45][46][47][48]. Location significantly influenced attitudes toward waste separation and recycling, [49,50] and employment rate also showed patterns in waste behavior [51].…”
Section: Logistic Regression Analysismentioning
confidence: 99%
“…Previous research on solid waste management behavior consistently highlighted income, education, location, and employment status as key factors. Studies using logistic regression analysis indicated that income predominantly influenced waste generation and households' willingness to minimize waste [43][44][45]; while education positively correlated with recycling behavior [44][45][46][47][48]. Location significantly influenced attitudes toward waste separation and recycling, [49,50] and employment rate also showed patterns in waste behavior [51].…”
Section: Logistic Regression Analysismentioning
confidence: 99%
“…Interestingly, urban poor communities with low income and education, those who make up a key faction within the informal sector, often engage in activities conducive to environment-friendly waste management behavior. For instance, some studies reflect that people in poverty practice recycling and waste source reduction while maintaining a proactive role as the main recyclers and source-reducers of waste in communities (Murad et al, 2012).…”
Section: A Frameworkmentioning
confidence: 99%